The effect of proximity to grocery stores and the pandemic on parents’ and youths’ perceptions of eating habits in predominately African American rural communities - Williams, Amanda; Newman, Sharlene D. (Frontiers in Nutrition, 2024)
Background: Rural communities have a disproportionately high level of childhood obesity along with high rates of food insecurity.To assess the eating habits of youth in predominantly African American rural communities and assess the association between proximity to a grocery store and eating habits as well as how the COVID-19 pandemic may have impacted eating habits.Methods: 203 youth and parents completed a 16-item survey. Analyses were performed to assess the effect of having a neighborhood grocery store as well as to compare responses between youth and parents.Results: Having a neighborhood grocery store was associated with increased consumption of vegetables (F(1,122)=41.56) and fruits (F(1,121)=65.05), decreased consumption of chips (F(1,125)=79.51) and a smaller percentage of overweight youth (χ 2 (1,125)=5.03). Parents underestimated the effect of the COVID-19 pandemic on youth eating habits (χ 2 (1,198)=17.88).Conclusions: Proximity to a grocery store significantly associated with eating habits and weight in the rural communities examined. Given the steady decrease in the number rural grocery stores over the past decade it is important to consider how to improve access to healthy foods in these communities.